Pengaruh Pemahaman Sistem Akuntansi, Kompetensi Sumber Daya Manusia, dan Partisipasi Masyarakat terhadap Akuntabilitas Pengelolaan Dana Desa - Almareta, Ambar; Nusantoro, Jawoto; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the influence of Accounting System Understanding, Human Resource Competence, and Community Participation on the Accountability of Village Fund Management in Sragi Subdistrict, South Lampung Regency. The research employs a quantitative approach using primary data. Data were collected through questionnaires distributed to 80 respondents, who are village officials in the region. The sampling technique used was saturated sampling, in which the entire population was used as the sample. Data analysis was conducted using SPSS. The results of the study show that Accounting System Understanding does not have a significant effect on the Accountability of Village Fund Management, while Human Resource Competence and Community Participation both have significant effects. Furthermore, simultaneously, Accounting System Understanding, Human Resource Competence, and Community Participation have a positive influence on the Accountability of Village Fund Management in Sragi Subdistrict, South Lampung Regency.